Morphological patterns and distribution of Inselbergs in Quixadá and Quixeramobim – Northeastern Brazil - Gomes, Eliomara Leite Meira; Maia, Rubson Pinheiro; Souza, Anna Sabrina Vidal de (Revista Brasileira de Geomorfologia, 2024)
Inselberg fields are found on several continents, including South America, North America, and Africa. In Brazil, one of the largest assemblages of these landforms is the Quixadá-Quixeramobim inselberg field, which is composed of 195 inselbergs organised in two clusters corresponding to the Quixadá and Quixeramobim granitic plutons. In general terms, studies related to spatial distribution and morphological patterns of inselbergs based on morphometric parameters are still scarce. The aim of this work is to analyse the distribution of inselbergs in relation to morphological and morphometric patterns and to point out the main factors influencing their distribution on granitic plutons, in order to support the understand of the evolution of these landforms. Radar and optical images with different spatial resolutions were used for the morphometric analysis of the inselbergs. Their boundaries were manually vectorised using GIS programs and their minimum and maximum heights were automatically extracted using an analysis and measurement tool inserted in the QGIS 3.28.4 Firenze software. Six core areas were identified with a high density of inselbergs, reaching 1,5 inselbergs per square kilometre. The distribution patterns are generally related to the geological/faciological characteristics of the plutons and their structural configuration.